ANALISIS MINAT MASYARAKAT DESA PAMIJAHAN, DESA PASAREAN DAN DESA GUNUNG SARI KECAMATAN PAMIJAHAN KABUPATEN BOGOR MENGGUNAKAN APLIKASI MOBILE BANKING PADA MASA PANDEMI COVID-19 - Ramadayanti, Alfi; Trihantana, Rully; Kusumaningrum , Ria (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
This research aims to analyze and explain the physical variables distancing and stay at home variables affect or not affect partially public interest in using mobile banking applications during the Covid-19 pandemic and to analyze and explain physical distancing variables and stay at home variables influencing or not simultaneously influencing people's interest in using mobile banking application during the Covid-19 pandemic. The sample of this study was 348 respondents, namely the people of Pamijahan Village, Pasarean Village and Gunung Sari Village. This study uses quantitative methods with multiple linear regression analysis and data collection using a questionnaire. The results of this study are physical distancing and stay at home have a significant effect on partial to public interest in using mobile banking applications in the future Covid-19 pandemic and physical distancing and stay at home affect simultaneously public interest in using mobile banking applications during the Covid-19 pandemic.